Differential modulation of S-nitrosoglutathione reductase and reactive nitrogen species in wild and cultivated tomato genotypes during development and powdery mildew infection - Jahnová, Jana (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 Elsevier Masson SAS. All rights reserved.